1987
DOI: 10.1007/bf00271459
|View full text |Cite
|
Sign up to set email alerts
|

Visualization on full spine radiographs of the anatomical connections of the centres of the segmental body mass supported by each vertebra and measured in vivo

Abstract: A gamma-ray scanner has been used to develop in vivo a rapid, noninvasive technique for the estimation of the mass of successive body scans, and the positions of the centres of those masses. The integrated data are computed to calculate the mass supported by each vertebra and the coordinates of the centre of these masses. These coordinates are transferred from the coordinate system of the gamma ray table to the coordinate system of the X-ray radiographs. In this way, the anatomical relations of the centres of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
59
1
9

Year Published

1992
1992
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(73 citation statements)
references
References 3 publications
4
59
1
9
Order By: Relevance
“…The pattern of gradual increase in compression force values between T1 and L5 is consistent and in close agreement with findings from a previous study [13]. However, Keller et al [34] reported a greater peak compression force (exceeding 842 N at T11/T12), compared to the mean, raw peak force in the current study of 388.8 ± 105.6 N (range: 228.6-695.5 N) at L4.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The pattern of gradual increase in compression force values between T1 and L5 is consistent and in close agreement with findings from a previous study [13]. However, Keller et al [34] reported a greater peak compression force (exceeding 842 N at T11/T12), compared to the mean, raw peak force in the current study of 388.8 ± 105.6 N (range: 228.6-695.5 N) at L4.…”
Section: Discussionsupporting
confidence: 93%
“…The greater compression force in the Keller et al [34] study may be attributable to greater body mass (mean 76.6 kg) of their participants, more significant vertebral deformities imposed onto their model, and relatively smaller shear forces. Compression force peaked in their study at T11/T12, compared to L4 in our study and previous studies [13,18]. Although net compression forces were not different between groups at the level of fracture, compression force in the fracture group exceeded that of non-fracture cases at the level below the fracture.…”
Section: Discussioncontrasting
confidence: 45%
“…Studies have confirmed that some structural features of the pelvis modulate and largely determine the amount of standing lumbar lordosis, as well as the sagittal pelvic alignment and spinopelvic balance [3,5,13,22]. These relationships have been documented in adult volunteers [3][4][5][6][7][8]22] and in patients with spinal disorders. The most important roentgenographic parameters of the sagittal balance of the spine in upright posture are well defined, and their normal physiological values have been reported [13,22].…”
Section: Introductionmentioning
confidence: 90%
“…The authors also emphasize the relationship of the spine to pelvic orientation changes and how they determine the spinal alignment as a whole. [9][10][11][12][13] Spino-pelvic sagittal balance is understood to be the relationship between the osteoarticular and myofascial structures of the spinal axis, the pelvis, and lower limbs directly related to postural sway.…”
Section: Introductionmentioning
confidence: 99%